2020
DOI: 10.1097/ccm.0000000000004707
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Ischemic and Hemorrhagic Strokes During Venovenous Extracorporeal Membrane Oxygenation: Analysis of Data From the Extracorporeal Life Support Organization Registry

Abstract: OBJECTIVES: Stroke is commonly reported in patients receiving venovenous extracorporeal membrane oxygenation, but risk factors are not well described. We sought to determine preextracorporeal membrane oxygenation and on-extracorporeal membrane oxygenation risk factors for both ischemic and hemorrhagic strokes in patients with venovenous extracorporeal membrane oxygenation support. DESIGN: Retrospective analysis. SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 27 publications
4
47
2
Order By: Relevance
“…Our meta-analysis showed an overall mortality of 36%, and this increased to 92% in patients with neurological events. A previous study, including 15,872 VV-ECMO patients (non COVID-19), showed a similar overall mortality (34%) and 73% mortality for patients with ICH, which is consistent with the findings from our study [11]. While it is not surprising that the presence of neurological events increased the risk of mortality, it is essential to emphasise the importance of a standardised neuromonitoring protocol and frequent neurological assessment for ECMO patients regardless of COVID-19 status [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our meta-analysis showed an overall mortality of 36%, and this increased to 92% in patients with neurological events. A previous study, including 15,872 VV-ECMO patients (non COVID-19), showed a similar overall mortality (34%) and 73% mortality for patients with ICH, which is consistent with the findings from our study [11]. While it is not surprising that the presence of neurological events increased the risk of mortality, it is essential to emphasise the importance of a standardised neuromonitoring protocol and frequent neurological assessment for ECMO patients regardless of COVID-19 status [22].…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated an overall prevalence of 5.9% for ICHs, 1.1% for ischaemic stroke and 0.3% for HIBI among 1,322 COVID-19 patients requiring ECMO support. Previously, a large cohort study using the Extracorporeal Life Support Organization registry database demonstrated that patients with VV-ECMO support for acute respiratory failure, without COVID-19, had 3.1% ICHs and 1.4% ischaemic strokes [11]. Similarly, a recent meta-analysis, pooling ECMO patient data from 1992-2015, showed a 7.1% overall prevalence of neurological events, with 3.6% of patients with ICH and 1.7% with ischaemic stroke [12].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the use of ECMO and a ventilator in critical COVID-19 patients may result in gastrointestinal bleeding. The bleeding in EMCO-supported patients may be due in part to the required high doses of heparin, mechanically high blood flow rates and circuit-induced coagulopathy (30)(31)(32). These patients may have a high incidence of bleeding despite the use of acid-suppressing agents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HIBIs, acute ischemic stroke (AIS) and intracranial hemorrhage (ICH) are major complications that increase mortality in patients supported with ECMO [76,84,85]. In patients treated with VA-ECMO, the prevalence of AIS is 3.3% and may be as high as 16% on autopsy [86,87].…”
Section: Ischemic Stroke and Intracranial Hemorrhage In Va-ecmomentioning
confidence: 99%